HUBUNGAN PENGETAHUAN IBU MENYUSUI TENTANG ASI EKSLUSIF DENGAN PEMBERIAN ASI EKSLUSIF DI DESA SEI SERINDAN KOTA TANJUNGBALAI TAHUN 2019 - ROSTINA AFRIDA POHAN (LP2MTBM MAKARIOZ, 2020)
Exclusive breastfeeding is the infant only breast-fed only, without the addition of other liquids for 6 months. Mother's knowledge about the advantages of breastfeeding and how breastfeeding is right to support mothers in breastfeeding success. This study aimed to breastfeeding relationship of knowledge about exclusive breastfeeding to exclusive breastfeeding in the village of Sei Serindan District of Tanjungbalai 2019. Type quantitative research with cross sectional approach. The population of nursing mothers with babies aged 0-24 months. The sample in this study using a total sample of 38 mothers with babies 0-24 bulan.Data Analysis Using Chi-square test.The results of the research that the majority of respondents 38 respondents less knowledgeable as much as 20 (52.6%) and 31 (81.6%) did not provide exclusive breastfeeding to their babies. Test results obtained statistical value of p = 0.000, it can be concluded there is a relationship of knowledge about breastfeeding Exclusive breastfeeding mothers with exclusive breastfeeding in the village of Sei Serindan District of Tanjungbala9 2019Advice to (1) the respondent for actively participating in Posyandu, health counseling in particular about exclusive breastfeeding and the class of pregnant women (2) For the Village Government needs to be done in collaboration with Health Officers to conduct counseling on exclusive breastfeeding (3) For researchers Further to researching important factor affecting the provision of exclusive breastfeeding.